IMPLEMENTASI MEDIA AUDIO VISUAL BERBASIS ANIMASI BAHASA ARAB DALAM PEMBELAJARAN MAHᾹRAH ISTIMᾹ’ - Tini, Cahya; Sidiq, Hamid (STIQ Amuntai, 2023)
Listening skill is a basic skill element for students who will start learning a foreign language. Therefore, the ability to listen is very important for teachers and students when teaching or learning Arabic as a foreign language. To achieve predetermined learning objectives, teachers need high creativity and innovation in using learning strategies or media, especially to develop listening skills. Learning media as a teaching tool that is relevant to teaching materials can make students motivated to learn. By using audio-visual media based on Arabic animation, learning Arabic can be made more interesting, simplify the learning process, increase students' motivation and enthusiasm for learning, and enable active learning of Arabic. This research is research that uses qualitative methods with a phenomenological approach using the theory of Miles & Huberman. Qualitative research is a study where researchers upload the actions and behaviour of objects by carrying out research steps such as observation, interviews, documentation, content analysis and other data collection methods. The results of his research show that there are 3 stages in the application of Arabic animation-based audio-visual media namely the first stage of preparation, namely by preparing a lesson plan. The second stage of the implementation of learning. The third stage of follow-up activities. The research results obtained show that using audio-visual media based on Arabic animation provides influential results for improving students' istima skills. Teachers are expected to use learning media more often in the process of teaching and learning activities.